2014
DOI: 10.1080/10942912.2013.853186
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Ketchup Sensory Texture Acceptability and Examination of Determining Factors as a Basis for Product Optimization

Abstract: The aim of this study was to examine possible usage of instrumental determination of selected texture parameters to estimate sensory texture acceptability of ketchups. Likewise, the authors focused on examination whether the consumer's perception of texture acceptability is connected to the selected factors related to the ingredients and production technology. Yet another aim was to describe the selected textural parameters of ketchups available in the European market. Within the frame of this study, 29 sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
0
12
0
1
Order By: Relevance
“…Several studies have been published on the evaluation of rheological/textural properties of tomato products like tomato juice, [30] tomato paste, [31][32][33][34] tomato sauce, [35] ketchup, [2,36,37] and ketchupprocessed cheese mixtures. [38] In addition, the effects of various types of hydrocolloids, [1,3,4,6,10] processing parameters, and the structural characteristics of tomato paste on the rheological/viscoelastic behavior of ketchup have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published on the evaluation of rheological/textural properties of tomato products like tomato juice, [30] tomato paste, [31][32][33][34] tomato sauce, [35] ketchup, [2,36,37] and ketchupprocessed cheese mixtures. [38] In addition, the effects of various types of hydrocolloids, [1,3,4,6,10] processing parameters, and the structural characteristics of tomato paste on the rheological/viscoelastic behavior of ketchup have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Ketchup texture is an essential factor in evaluating consumer acceptance (Zhang, Xie, & Zou, 2019). The texture includes several properties of which consistency and viscosity are usually considered as the main aspects of the quality of tomato products (Tauferova et al, 2015). Viscosity is a valuable physical property.…”
Section: Introductionmentioning
confidence: 99%
“…Ketchup having varying in nutritional and sensory quality in European market. Sensory quality is of the primary importance as the majority of consumers are most aware of this quality aspect [6].…”
Section: Introductionmentioning
confidence: 99%
“…Karla Ariane et.al study show that the quality of tomato paste or products in terms of ascorbic acid, color and consistency affects exposer of sunlight and industrial processing chain [10]. One research has shown that novel processing technology would yields high quality, better nutrients and longer shelf life of tomato products [11]. The tomato cultivar used during the processing of tomatoes is the most important factor which will be related to product consistency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation